Multinational Enterprises, Sustainability and Innovation - Lee, Jeoung Yul; Nayir, Dilek Zamantili; Chen, Charles (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on MNEs, sustainability, and innovation contains a collection of 13 papers that address several subjects that are on related themes. The authors of these contributions study the boundaries of the previous literature on these relevant topics by providing insightful findings and review, as well as proposals for future research ideas in various contexts. For this Special Issue, we invited both conceptual and (qualitative and quantitative) empirical articles, as well as literature reviews and meta-analysis articles from a range of fields; these included not only business and management, but also sociology, political science, psychology, economics, and economic geography, among others.